Development of Ethnomathematics-Based Numeracy Literacy Questions in Peci Tapis Lampung - Linuhung, Nego; Sudarman, Satrio Wicaksono; Agustina, Rina (Universitas Muhammadiyah Mataram, 2025)
The low contextual relevance of conventional mathematics learning materials often results in limited student engagement and understanding, especially in diverse cultural settings. To address this gap, this study aims to develop valid, practical, and effective ethnomathematics-based numeracy literacy questions by integrating the cultural elements of Peci Tapis Lampung into mathematics instruction. The research employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). In the development phase, the questions were validated by four experts in material, design, and assessment using expert validation sheets. Student responses were measured through a practicality questionnaire. Quantitative data from expert validation were analyzed using descriptive statistics to determine the validity level, while student response data were processed to assess practicality. The validation results indicated that the questions were